Knowledge management process as a predictor on the organizational performances in Dubai government departments - Nek Kamal Bin Yeop Yunus (Tanjong Malim, 2019)
Knowledge management process as a predictor on the organizational performances in Dubai government departments by Nek Kamal Bin Yeop Yunus